The Effect Of Green Bond Towards Energy Transition And Firm Performance In Emerging Market - Ichramsyah Fajar Hatta (Cakrawala Repositori IMWI, 2023)
The study aims to inquire how green financing influence renewable energy dependence and renewable energy transition in ASEAN, using electric utilities company as the main sample. This paper therefore addresses the question of whether and how green finance (with the proxy of issued green bonds [GBs] promotes energy efficiency (with the proxy of energy intensity) in the ASEAN member countries. The objective of this study is to determine how green loans or green bonds can hasten the energy transition in a sampling nation in the years 2020–2022. This Research running the data from the Eikon Refintiv database that details the purpose of green bond issues using regression analysis. This study cover different public and private company in electric utilities industry. To the best of author’s knowledge, there has not been any in-depth study focusing on the relationship between green financing and energy transition for the case of electric industries company in ASEAN 2020-2022. this research will offer valuable insights to decision-makers in business and government sectors, with the aim of understanding the impact of green bonds on expediting a nation's transition towards sustainable energy.